Effect of Career Development and Employee Engagement on Employee Performance of PT. POS Indonesia (Persero) - Usep Deden Suherman; Eeng Ahman; Disman Disman; Rofi Rofaida (Jurnal Manajemen Universitas Bung Hatta, 2023)
ABSTRACT The purpose of this study is to determine and analyze the impact of career development and employee engagement on employee performance, either separately or simultaneously. The survey methods used in this study are descriptive and explanatory. The research was carried out on 87 employees PT Indonesia Pos (Persero). The saturated sampling technique was used for sampling. Multiple Regression Analysis was used to analyze the data. According to the study's findings, career development and employee engagement have a combined or partial impact on employee performance. Furthermore, the determinant value is 0.800, indicating that career development and employee engagement can account for 80% of employee performance. Other factors accounted for 20% of the variance. Keywords: Career Development, Employee Engagement, Employee Performance